2018
DOI: 10.1177/0023830918761489
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cyrillic on Native English Speakers’ Phono-lexical Acquisition of Russian

Abstract: We investigated the influence of grapheme familiarity and native language grapheme-phoneme correspondences during second language lexical learning. Native English speakers learned Russian-like words via auditory presentations containing only familiar first language phones, pictured meanings, and exposure to either Cyrillic orthographic forms (Orthography condition) or the sequence (No Orthography condition). Orthography participants saw three types of written forms: familiar-congruent (e.g., -[kom])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…By contrast, other researchers have reported no beneficial effect of exposure to orthographic input on the acquisition of a novel phonological contrast (Durham, Hayes-Harb, Barrios, & Showalter, 2016;Hayes-Harb & Hacking, 2015;Pytlyk, 2011;Showalter & Hayes-Harb, 2015;Simon, Chambless, & Kickhöfel Alves, 2010) or have demonstrated that orthographic input may interfere with the acquisition of target-like L2 phonological representations, particularly when the written input provides learners with "misleading" information about the phonological forms of new words. Interference effects have been reported when L2 orthographic conventions differ from those of the native language (L1; Bassetti, 2006), when grapheme-phoneme correspondences (i.e., the mapping[s] between grapheme and phoneme) are different in the L1 and L2 (Hayes-Harb & Cheng, 2016;Hayes-Harb et al, 2010;Showalter, 2018), or when the L1 and L2 differ in whether or not familiar graphemes signal a contrast (Escudero et al, 2014). Other factors, including the degree of perceptual difficulty posed by the contrast (Escudero, 2015) and the transparency of the L2 writing system (Mok, Lee, Li, & Xu, 2018), have also been found to modulate written input effects.…”
Section: Orthographic Input In L2 Phonolexical Developmentmentioning
confidence: 99%
“…By contrast, other researchers have reported no beneficial effect of exposure to orthographic input on the acquisition of a novel phonological contrast (Durham, Hayes-Harb, Barrios, & Showalter, 2016;Hayes-Harb & Hacking, 2015;Pytlyk, 2011;Showalter & Hayes-Harb, 2015;Simon, Chambless, & Kickhöfel Alves, 2010) or have demonstrated that orthographic input may interfere with the acquisition of target-like L2 phonological representations, particularly when the written input provides learners with "misleading" information about the phonological forms of new words. Interference effects have been reported when L2 orthographic conventions differ from those of the native language (L1; Bassetti, 2006), when grapheme-phoneme correspondences (i.e., the mapping[s] between grapheme and phoneme) are different in the L1 and L2 (Hayes-Harb & Cheng, 2016;Hayes-Harb et al, 2010;Showalter, 2018), or when the L1 and L2 differ in whether or not familiar graphemes signal a contrast (Escudero et al, 2014). Other factors, including the degree of perceptual difficulty posed by the contrast (Escudero, 2015) and the transparency of the L2 writing system (Mok, Lee, Li, & Xu, 2018), have also been found to modulate written input effects.…”
Section: Orthographic Input In L2 Phonolexical Developmentmentioning
confidence: 99%
“…It is expected that learners, at some stage, map Russian graphemes and phonemes in a targetlike manner, but whether this is true has not been empirically found. Finally, Showalter (2018), Comer and Murphy-Lee (2004), and Bown et al (2007) present evidence that Russian GPCs are difficult for naïve and beginner learners. It is expected that learners with more Russian experience will be less affected by “misleading” OI.…”
Section: Introductionmentioning
confidence: 98%
“…Showalter (2018) investigated the effects of grapheme familiarity and congruence on native English speakers’ ability to make inferences about the phonological forms of L2 pseudo-Russian words. During a word-learning phase, participants heard auditory forms of words, saw pictured meanings, and either saw a meaningless sequence of letters (i.e., <XXX>) or saw Cyrillic forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthography has been widely shown to influence L2 perception and/or word form learning. Orthography can have a facilitating (e.g., Showalter & Hayes-Harb, 2013), mixed (e.g., Detey & Nespoulous, 2008;Escudero, 2015), negative (e.g., Bassetti, 2017;Hayes-Harb, Brown, & Smith, 2018;Mathieu, 2016;Showalter, 2018) or null (Simon, Chambless, & Kickhöfel Alves, 2010) effect.…”
mentioning
confidence: 99%